2013
DOI: 10.1002/clen.201200099
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial and Enzyme Activities Response to Pollution Near an Aluminium Smelter

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
2
18
1
1
Order By: Relevance
“…However, S1 shared the lowest microbial activity, al though HMs concentrations in this sample were the lowest. These results were contrary to some studies, which reported negative relationships between HMs concentrations and soil microbial activities [10,11]. Correlation coefficient analysis was performed to find the possible relationships between physicochemical parameters and microbial activity related parameters, and results were shown in Table 3.…”
Section: Soil Microbial Activitiescontrasting
confidence: 62%
See 1 more Smart Citation
“…However, S1 shared the lowest microbial activity, al though HMs concentrations in this sample were the lowest. These results were contrary to some studies, which reported negative relationships between HMs concentrations and soil microbial activities [10,11]. Correlation coefficient analysis was performed to find the possible relationships between physicochemical parameters and microbial activity related parameters, and results were shown in Table 3.…”
Section: Soil Microbial Activitiescontrasting
confidence: 62%
“…Lots of studies had been conducted to analyze the effects of HMs on soil microbial community structure and functions, but contrasting results were reported in the literature. Some reported that long-term HMs contamination reduced soil microbial activity and diversity, reflecting the toxic effects of HMs on soil microbial community [10,11]; while others reported that activity of a well-adapted microbial community in heavily contaminated soil was not obviously affected by HMs contaminations [12,13]. Moreover, under natural conditions, metal effects on soil microorganisms are influenced by soil properties, such as organic matter (OM) content, pH, and the availability of N, P, and K [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is clearly a need to address this lack of knowledge, since (for instance) SOM is a major substrate for soil organisms, thus SOM contents and potential soil respiration rates are highly correlated . Numerous soil microbial and enzyme activities are involved in SOM decomposition , and thus play significant roles in environmental control of F CO2 . For instance, soil microbial biomass carbon (MBC) accounts for ca.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of fluoride in bark and leaves of forest trees around the aluminium plant in Norway was evaluated [6]. The soil microbial and enzyme activities response to pollution near an aluminium smelter in Žiar nad Hronom (central Slovakia) were also studied [7]. Research has been conducted on the effects of air pollution, for example of heavy metals in beech stands and in beech leaf litter in relation to the health status of beech stands investigated in Poland [8,9].…”
mentioning
confidence: 99%
“…Based on the number of scientific outputs which pointed at the negative impact of pollutants from Žiar smelter (defoliation: [20], physiology -chlorophyll, fluorescence: [21], herbs and fungi: [22], soil: [7,23], forest stand: [24]), our aim was to assess this effect on the occurrence of the necrotic disease of mature beech stands.…”
mentioning
confidence: 99%